Precision Neuromuscular Block Management for Neural Monitoring During Thyroid Surgery. Issue 12 (26th November 2021) - Lu, I-Cheng; Wu, Sheng-Hua; Chang, Pi-Ying; Ho, Pi-Yang; Huang, Tzu-Yen; Lin, Yi-Chu; Kamani, Dipti; Randolph, Gregory W.; Dionigi, Gianlorenzo; Chiang, Feng-Yu; Wu, Che-Wei
Abstract: Introduction: Titration of neuromuscular block (NMB) plays a key role in intraoperative recurrent laryngeal nerve monitoring during thyroid surgery. The combination of neuromuscular blocking agent and timely partial reversal of NMB was investigated in both animal experiments and clinical neuro-monitored thyroidectomy. Methods: In animal experiments, 8 piglets received sugammadex to assess the laryngeal EMG recovery after rocuronium-induced NMB. In clinical monitored thyroidectomy, 40 patients each were allocated to conventional group and sugammadex group. Conventional group received rocuronium 0.3 mg/kg at anesthesia induction, while sugammadex group received partial NMB recovery protocol- 0.6 mg/kg of rocuronium at anesthesia induction and 0.5 mg/kg of sugammadex. Main outcome was assessed by first (V1) and final (V2) EMG signal induced by vagal stimulation. Results: In the porcine model, 50% recovery of laryngeal EMG amplitude was achieved at 16.8 ± 1.9 and 6 ± 2.7 minutes respectively after 0.5 and 1 mg/kg of sugammadex ( p < 0.01). In monitored thyroidectomy, EMG amplitudes at V1 in group S and group C were 1214 ± 623 and 915 ± 476 μV, respectively ( p = 0.02). Positive and adequately high EMG amplitudes were observed at the early surgical stage for all patients. Sugammadex groups were superior to conventional group in EMG tube placement (p < 0.001). Conclusion: Both porcine model and clinical application showed that precise NMB management by low-dose sugammadex was effective for intraoperative neural monitoring (IONM). The regimen ensured optimal conditions for tracheal intubation and timely neuromuscular function restoration for high-quality EMG signal.